Language, Sustainability and Social Responsibility: A Theoretical Exploration of ESL in Malaysia - Suzanah Selamat; Fariza Puteh Behak; Noor Saazai Mat Saad; Ramiaida Darmi; Hazleena Baharun; Engku Muhammad Syafiq Engku Safruddin; Norhaili Massari (Universiti Sains Islam Malaysia, 2026)
International Conference of Language & Education (iLEC2025): Empowering Language and Education to Develop Madani Generation in the Era of Artificial Intelligence (AI) 17 & 18 November 2025 Organized by Universiti Sains Islam Malaysia